Decline in cold-water coral growth promotes molluscan diversity: A paleontological perspective from a cold-water coral mound in the western Mediterranean Sea - Korpanty, Chelsea A.; Hoffman, Leon; Portilho-Ramos, Rodrigo da Costa; Titschack, Jürgen; Wienberg, Claudia; Hebbeln, Dierk (Frontiers in Marine Science, 2023)
Framework-forming scleractinian cold-water corals (CWCs) act as ecosystem engineers, building and supporting biodiversity hotspots in the deep sea worldwide. While spatial patterns and drivers of species distributions have been evaluated on modern CWC reefs, little is known about how reef diversity is affected by habitat variability over geologic time – the scale at which CWC reefs initiate, thrive, and decline. Using three CWC reef sediment cores as species diversity archives, we investigated temporal trends of molluscan diversity over the last 13 kyr from a CWC mound in the Alboran Sea (western Mediterranean Sea) to evaluate (a) how spatial patterns of CWC-associated diversity are recorded in reef sediments, (b) the potential of CWC reefs as biodiversity hotspots when coral growth is flourishing and when it is not, and (c) which palaeoceanographic conditions or habitat characteristics may be driving biodiversity. Our results reveal that at the ecosystem scale ecological differences between CWC habitats are more pronounced than ecological signatures of molluscan assemblages associated with intervals of CWC framework (flourishing growth) or non-framework (negligible CWC growth). However, within habitats, significant differences emerge between these assemblages with lower molluscan diversity associated with flourishing CWC growth. Significant negative correlations between molluscan diversity and palaeoceanographic conditions conducive for CWC growth (high food availability, strong hydrodynamics, optimal bottom-water temperatures and salinities, and high aggradation rates indicative of flourishing CWC growth also imply that CWC growth and relevant environmental conditions contribute to reduced molluscan diversity. Additionally, high coral volume, used here as a proxy for habitat structural complexity, is positively correlated with molluscan diversity just as high habitat complexity is in living CWC reefs. Altogether, these patterns detected over geologic time resemble those observed spatially across living CWC reefs today – where competition with resources, particularly food, prevents high reef biodiversity in the immediate vicinity of dense living CWC colonies. Overall, our study demonstrates that (1) ecological paradigms of living CWCs are preserved in their sedimentary record, (2) flourishing CWC growth and conditions promoting CWC growth drive habitat-scale diversity patterns, and (3) a geological approach can be applied to study long-term diversity dynamics in CWC ecosystems.